Model for predicting academic stress among students of technical education in India - Verma, Garima (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this paper is to examine the mental stress among the students studying in higher education at the college level, especially those who are taking technical education in India. Also, the paper will identify the factors that affect the mental condition of students who have just taken admission from traditional school education to technical education in college or university. Data from 2500 students studying at graduation level in various technical education colleges and universities in northern India, has been collected using a structured questionnaire through online and offline channels. An ensemble prediction model to know the stress level of technical students has been proposed using the Machine learning technique. The findings of the study revealed that the main factors which influence the mental stress and depression in the students who are new to technical education are heavy workload, lack of support of family and friends, attendance pressure, cooperation with teachers, placement and lack of extra-curricular activities. This study is an effort to analyse the stress level of the students at the early stage so that different types of precautions can be taken by their parents, teachers, friends, college management, etc. to help them in managing their depression, stress, and anxiety. This is the first study as per the literature that explores the stress of students enrolled in technical education in India. The study identifies various factors that are of concern and that affect the stress level in students.